2021
DOI: 10.1093/isd/ixab005
|View full text |Cite
|
Sign up to set email alerts
|

Toward a Stable Global Noctuidae (Lepidoptera) Taxonomy

Abstract: Noctuidae are one of the world’s most diverse, ecologically successful, and economically important animal lineages with over 12,000 species in ~1,150 genera. We inferred a phylogeny using eight protein-coding genes for the global fauna, greatly expanding upon previous attempts to stabilize Noctuidae higher classification by sampling 341 genera (nearly half represented by their type species) representing 70/76 widely recognized family-group taxa: 20/21 subfamilies, 32/35 tribes, and 18/20 subtribes. We evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 49 publications
2
26
0
Order By: Relevance
“…Despite the limited diversity of Neotropical Noctuidae, their taxonomy and systematic composition remains poorly known, essentially unchanged from the time of Hampson's (1898Hampson's ( -1913 artificial classification (for a review of historic changes to noctuid classification, see Mitchell et al (2006) and references therein). Exceptions include recent molecular studies that have incorporated a limited number of Neotropical genera, nonetheless making significant inroads to clarifying the major Noctuidae lineages present in the Neotropics, such as the discovery of the basal subfamily Dyopsinae and its bizarre constituent genera (Zahiri et al 2013;Keegan et al 2021), the equally odd Vespola Walker group of genera related to Bagisarinae (Zahiri et al 2013), and the circumscription of entirely new subfamilies such as Cobubathinae and Cropiinae (Keegan et al 2021). As part of ongoing work to revise the genera of Nearctic Apameini and placing Neotropical genera into a systematic framework, examination of the genus Trachea Ochsenheimer revealed that few, if any, of the Neotropical species truly belong to this Holarctic genus, and led to the surprising find that "Trachea" altivolans belongs to the Apameini.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the limited diversity of Neotropical Noctuidae, their taxonomy and systematic composition remains poorly known, essentially unchanged from the time of Hampson's (1898Hampson's ( -1913 artificial classification (for a review of historic changes to noctuid classification, see Mitchell et al (2006) and references therein). Exceptions include recent molecular studies that have incorporated a limited number of Neotropical genera, nonetheless making significant inroads to clarifying the major Noctuidae lineages present in the Neotropics, such as the discovery of the basal subfamily Dyopsinae and its bizarre constituent genera (Zahiri et al 2013;Keegan et al 2021), the equally odd Vespola Walker group of genera related to Bagisarinae (Zahiri et al 2013), and the circumscription of entirely new subfamilies such as Cobubathinae and Cropiinae (Keegan et al 2021). As part of ongoing work to revise the genera of Nearctic Apameini and placing Neotropical genera into a systematic framework, examination of the genus Trachea Ochsenheimer revealed that few, if any, of the Neotropical species truly belong to this Holarctic genus, and led to the surprising find that "Trachea" altivolans belongs to the Apameini.…”
Section: Introductionmentioning
confidence: 99%
“…As part of ongoing work to revise the genera of Nearctic Apameini and placing Neotropical genera into a systematic framework, examination of the genus Trachea Ochsenheimer revealed that few, if any, of the Neotropical species truly belong to this Holarctic genus, and led to the surprising find that "Trachea" altivolans belongs to the Apameini. Trachea is currently placed in the tribe Dypterygiini (Lafontaine and Schmidt 2010;Keegan et al 2021). A new genus is herein described to accommodate "Trachea" altivolans and to facilitate future study of the taxonomy and biogeography of the New World Apameini.…”
Section: Introductionmentioning
confidence: 99%
“…The genus Himalaea Hreblay & L. Ronkay, 1998 belongs to the subtribe Psaphidina of the tribe Psaphidini of the subfamily Amphipyrinae (Wagner et al 2008;Lafontaine & Schmidt 2010;Ronkay et al 2011;Zahiri et al 2011;Keegan et al 2019Keegan et al , 2021. It was erected to include the only species Himalaea unica Hreblay & L. Ronkay, 1998 described by a single male from south-eastern Xizang Autonomous Region of China (Hreblay et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Dasypolia Guenée, 1852 is a large noctuid genus distributed in the Palearctic region and reaching its greatest diversity in high mountain areas of Asia. The genus belongs to the subtribe Antitypina of the tribe Xylenini of the subfamily Noctuinae (Lafontaine and Schmidt 2010;Zahiri et al 2011;Keegan et al 2021). Many species of Dasypolia were described during the last two decades (Nupponen and Fibiger 2006;Ronkay et al 2010;Benedek et al 2011Volynkin 2012;Ronkay et al 2014).…”
Section: Introductionmentioning
confidence: 99%